FINANCIAL DISTRESS SEBAGAI PEMODERASI PENGARUH FEE AUDIT PADA AUDITOR SWITCHING - Diandika, Kadek Harum; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
The purpose of this research is to specify how audit fee impact auditor switching. In addition, to moderate the effects of financial distress audit fees on auditor switching. The location of this research is manufacturing companies listed on the Stock Exchange in 2012-2014 with the sample collection method using purposive sampling techniques. Total manufacturing company listed on the Stock Exchange as many as 142 companies and acquired sample number of 63 companies. There are several techniques of analysis used in this study is a logistic regression analysis and Moderate Regression Analysis. The results of this study indicate that the audit fee positive effect on the auditor switching. This means that the higher fee offered auditor audit the auditor switching in the company will increase. Financial distress memperkuat hubungan antara fee audit and auditor switching. This means companies that have a high audit fee and are experiencing financial distress it tends.
Keywords: Auditor switching, fee audit, financial distress